Seasonal, meteorological and geophysical factors influence on acute cardiovascular events - S. Ya. Dotsenko; A. V. Afanasyev; K. K. Malashenko; V. A. Yevtushenko; T. V. Kravchenko; I. I. Tokarenko; G. Ya. Medvedchuk; M. V. Shevchenko (Zaporožskij Medicinskij Žurnal)
The aim of research was to explore the influence of seasonal, meteorological and geophysical factors on acute cardiovascular events in the practice of emergency.